Effects of Trehalase on the Gene Expression of the Reproductive Regulation Pathway Network and Triglyceride Metabolism in Nilaparvata lugens (Stål) - Bin Tang; Yuxin Ge; Yongkang Liu; Liwen Guan; Ye Han; Yang Zhu; Gao Hu; Yan Wu (Insects, 2025)
The high reproductive performance of Nilaparvata lugens (Stål) (Hemiptera: Delphacidae) is one of the key factors contributing to its serious damage. Studies have demonstrated that trehalose hydrolysis, catalyzed by trehalase (TRE), plays an important role in the reproductive regulation of N. lugens. However, it remains unclear how TRE regulates the reproduction of N. lugens. To address this question, the current study was designed to investigate the effects of TRE on the reproductive regulatory network of N. lugens. Specifically, RNA interference (RNAi) was conducted by injecting double-stranded RNA (dsRNA) targeting the TRE genes, and a trehalase inhibitor, validamycin, was used to suppress TRE activity. Subsequently, the relative expression levels of key genes involved in the reproductive regulatory pathway, as well as the triglyceride content in the fat body and ovary, were determined. The results indicated that both dsTREs and validamycin treatment decreased the relative expression of Vitellogenin (Vg) without affecting the expression of its receptor, VgR. However, their impact on the reproductive regulatory network differed: dsTREs injection did not affect the relative expression of JHAMT and Met in the juvenile hormone signaling pathway, but resulted in the upregulation of USP and TOR, and inhibition of InR2 and S6K. In contrast, validamycin injection inhibited the expression of Met, USP, EcR, InR1, TOR, and S6K. Both dsTREs and validamycin inhibited the expression of Fas, but only validamycin decreased the ovarian triglyceride content. These findings suggest that the inhibition of TRE leads to alterations in reproductive regulatory signals, thereby reducing the reproductive capacity of N. lugens.